Fracture resistance of incisor teeth restored using fibre-reinforced posts and threaded metal posts: effect of post length, location, pretreatment and cementation of the final restoration - Schmitter, Marc; Lippenberger, Sven; Rues, Stefan; Gilde, Herbert; Rammelsberg, Peter (International endodontic journal, 2010)
The hypothesis of this study was that the fracture load of incisor teeth restored using short, threaded, parallel-sided posts (TMP) is, under special conditions, not inferior to that of teeth restored using long TMPs or fibre-reinforced posts (FRP).